Exploration of bacteriophages from waters in Palembang, Indonesia as biocontrol of antibiotic-resistant Escherichia coli - RIRI NOVITA SUNARTI; POEDJI LOEKITOWATI HARIANI; SRI BUDIARTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sunarti RN, Hariani PL, Budiarti S. 2023. Exploration of bacteriophages from waters in Palembang, Indonesia as biocontrol of antibiotic-resistant Escherichia coli. Biodiversitas 24: 6069-6081. The emergence and dissemination of antibiotic-resistant bacteria in the aquatic environment demand for utilization of bacteriophage (phage) therapy as an ecologically conscious alternative to mitigate the consequences of drug resistance. The presence of antibiotic-resistant Escherichia coli (E. coli) in the river of Palembang City is a matter of concern for public health. It is imperative to explore the potential of phages as biocontrol agents against antibiotic-resistant E. coli sourced from the rivers of Palembang City. The effectiveness of the phage was then evaluated in managing antibiotic-resistant E. coli in contaminated water. The exploration resulted in the acquisition of 12 phage isolates from various water sources. Specifically, three phage isolates were obtained from Kedukan River (FgSK11.2, FgSK22.2, FgSK31.3); three phage isolates were obtained from Buah River (FgSB13.2, FgSB13.3, FgSB33.1); and six phage isolates were obtained from PU River (FgPU11.2, FgPU11.3, FgPU31.3, FgPU33.1, FgPU33.2, FgPU33.3). The isolates have demonstrated the ability to lyse antibiotic-resistant E. coli bacteria. The findings indicate that bacteriophages can mitigate pollution in collected water samples. The phage cocktail utilized effectively inhibited the growth of antibiotic-resistant E. coli, reducing their population. Furthermore, the treatment resulted in satisfactory water quality improvements by reducing the Fe and Pb levels. The results of this study show a significant advancement in the use of phages as a first step in addressing the problem of E. coli pathogen-caused water pollution in Palembang City.